Contextual Bible Study Notes on Luke 4 16-22 - Riches, John Kenneth 1939- (2006)
The article studies an account of teaching by Jesus Christ in Luke 4:16-22. The story focuses on the sense of expectation from Jesus which the people evidently shared. It also provides a summary of His preaching in first century Galilee, Israel. The passage could inspire people to become more involved in movements for international justice and for greater justice and equality in society.
Keywords: Bibel; Bible. Luke; CHRISTIANITY & justice; Galilee (Israel); Israel; Jesus Christ -- Teachings; Preaching